The hydrology and preservation condition in the flat-topped burial mound: Klangshøj at Vennebjerg in Vendsyssel - Breuning-Madsen, Henrik; Henriksen, Peter Steen; Kristensen, Jeppe Ågård; Jessen, Maria; Ekman, Rasmus (Danish Journal of Archaeology, 2016)
Klangshøj is a flat-topped burial mound similar to the Royal Jelling mounds, although smaller. The myths tell that a well has existed on top of the mound as at Jelling and a spring had flown at the base of the mound. In order to verify the myths and a similar hydrology in Klangshøj as found in Jelling, several borings have been carried out in a north-south line across the mound. The investigation showed that Klangshøj is built of sods mainly harvested from heathland. The sods are of different grain sizes from fine sand to clay. The preservation conditions were excellent in three of the six borings, where undecomposed plant remnants, occasionally greenish, were observed. A 14C-dating showed that the mound was built in the Viking Age. The hydrology in Klangshøj is the same as in the Jelling mounds, with a permeable bioturbation zone covering almost impermeable, distinct sod layers. This form a perched groundwater table in the transition zone, which keeps the distinct sod layer below anaerobic, i.e. the preservation conditions extremely favourable. The perched water table drains internally as in the Jelling mounds, and there are no current nor fossil evidence to suggest a spring was ever present at the foot slope, as the local legend suggests. Moreover, it seems unlikely that a well, similar to the one on the Jelling mound, has existed on the top of the north-facing slope, as the amount of water the well would have been able to collect is little.